2020
DOI: 10.1186/s12891-020-3064-4
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between the efficacy of stem cell therapy for osteonecrosis of the femoral head and cell viability

Abstract: Background: Osteonecrosis of the femoral head (ONFH) is a common disease that greatly affects the quality of life of patients. Repair of the necrotic area is key to successful treatment. Currently, the combination of stem cell transplantation and decompression is used clinically to promote the repair of necrotic areas based on the characteristics of stem cells. However, a considerable number of patients do not achieve a satisfactory outcome in terms of repair of the femoral head necrotic area, and it is very i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 37 publications
0
2
0
1
Order By: Relevance
“…Wu et al . treated 30 patients with CD using a 6.5-mm drill, curettage and BMAC soaked in collagen sponge and showed significant improvement in HHS and VAS score after mean follow-up of 9 months (HHS: 84.66, VAS: 1.91; P < 0.05) [ 35 ]. The necrotic area was evaluated by MRI, and repair ratio was calculated by dividing the difference of this area before and after 9 months of surgery, by the area before surgery and multiplying the value by 100.…”
Section: Resultsmentioning
confidence: 99%
“…Wu et al . treated 30 patients with CD using a 6.5-mm drill, curettage and BMAC soaked in collagen sponge and showed significant improvement in HHS and VAS score after mean follow-up of 9 months (HHS: 84.66, VAS: 1.91; P < 0.05) [ 35 ]. The necrotic area was evaluated by MRI, and repair ratio was calculated by dividing the difference of this area before and after 9 months of surgery, by the area before surgery and multiplying the value by 100.…”
Section: Resultsmentioning
confidence: 99%
“…In most studies reported to date, the improvement in clinical symptomatology and functionality of the hip is a constant, although the values are notably higher than those obtained in our clinical trial. Sen et al [ 31 ], for example, found results over 76 points on the HHS at 12 months, and Wu et al [ 32 ] found a mean of 84.66 in the HHS and a VAS of 1.91 after nine months of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Через 9 месяцев после оперативного вмешательства оценка по шкале Harris'а достигла 84,66 баллов, оценка по ВАШ боли снизилась до 1,91 на фоне уменьшения объёма очага некроза. На протяжении периода наблюдения ни одному из 30 пациентов не потребовалось ТЭТС [25]. Вероятно, такие результаты, в первую очередь, можно объяснить малым периодом наблюдения за пациентами.…”
Section: результаты и обсуждениеunclassified